Pengaruh Budaya Sekolah dan Kompetensi Guru terhadap Mutu Pendidikan di SMP Negeri Se-Kecamatan Randudongkal Kabupaten Pemalang - Mustowiyah Mustowiyah; Ngurah ayu Nyoman Murniati; Sunanda Sunanda (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2017)
The purpose of this study are: (1) Finding out how much is the influence of school culture on educational quality, (2) Finding out how much is the influence of the competence of teachers to the quality of education, and (3) Finding out how much is the influence of school culture and teacher competence collectively to the quality of education. The population in this study was all State junior high school teachers throughout the Sub District of Randudongkal District of Pemalang, the number of the population wasÂ 225 people, and the samples were selected using proportionate random sampling technique as many as 69 people. The data analysis was using descriptive analysis, the test of data requirements, and analysis, / regression test. The test results for the prerequisite of research data it is concluded that the data were normally distributed, homogeneous, linear, does not incur multicollinearity and does not incur heteroskedasticity. While from the hypothesis test, it can be concluded that there is a significant effect on the school cultures to the quality of education in the total of 0.911 with a contribution of 82.8%. There is a significant effect of teacher competence on the quality of education at 0.790 with a contribution of 61.9%. There is the influence collectively on the School Culture and Teachers Competence against Education Quality of 0.977 with a contribution of 95.3%